The effect of neonatal visit to exclusive breastfeeding - Chori Elsera (Alma Ata University Press, 2018)
ABSTRACT Background: The infant mortality rate in Indonesia is still very high at around 32 per 1,000 live births. This number is still very far from the MDGs by 2015 that is 23 per 1,000 live births. Indonesia ranks 10 out of 18 countries in ASEAN. Coverage of exclusive breastfeeding in Indonesia is still low and decreasing every year. It is inversely proportional to the scope of neonates visits to 90% more. Activities carried out during the visit of neonates among other vital signs checks, counseling and exclusive breastfeeding infant care, vaccination, treatment and referral of cases.Objectives: To determine the influence of neonatal visits to exclusive breastfeeding, evaluate the relationship of education, knowledge, work, place and birth attendants, gestational age and birth weight, family support exclusive breastfeeding.Methods: An observational study and case-control design were used with a quantitative approach. The samples in this study were mothers with babies aged 6 to 9 months at the time of the study that met the inclusion criteria. The total sample were 158 respondents, that were divided into 2 groups, 79 in the case group and 79 in the control group. The sampling technique with simple random sampling. Data was collected by was conducted interviews with questionnaires and secondary data. Analysis of the data used univariate analysis with frequency distribution table, with Chi-square bivariate and multivariate logistic regression.Results: The result of this study showed 76.6% of respondents were worker, 90.5%, 63.95 had higher education history. There was a significant relationship between neonatal visit with exclusive breastfeeding with p = 0.026 (OR 0.488, 95% CI 0.259 to 0.92). External variables that most influence on exclusive breastfeeding was working with a value of p = 0.016 (OR 2.878, 95% CI 1.217 to 6.805).Conclusions: Visits neonates influencedexclusive breastfeeding in Klaten. Employment is the most influential factor for exclusive breastfeeding.KEYWORDS: exclusive breastfeeding, neonates, visits neonates